Antiphospholipid Syndrome–Not a Noninflammatory Disease - de Groot, Philip G.; Urbanus, Rolf T. (Seminars in Thrombosis and Hemostasis, 2015)
The autoimmune disease antiphospholipid syndrome (APS) is characterized by thrombosis or pregnancy morbidity in patients with persistent antiphospholipid antibodies (aPLs). Although inflammation is not a key feature of the clinical presentation of the syndrome, there are indications that the inflammatory response plays an important role in APS. The major antigen of aPLs, the plasma protein β2-glycoprotein I, is involved in clearance of microparticles and in the innate immune response. In light of these physiological functions, the formation of antibodies against the protein is easily understood, as antibodies might augment the clearance reaction. In addition, inflammatory mediators are thought to play a role in the activation of leukocytes and the induction of endothelial dysfunction in APS. Moreover, evidence for a role of complement activation in the pathogenesis of the syndrome is accumulating. This review will provide an overview of current knowledge on the physiological function of β2-glycoprotein I, the formation of autoantibodies against β2-glycoprotein I and will explore the contribution of inflammation to the clinical manifestations of APS.
Keywords: inflammation; β2-glycoprotein I; infection; complement; antiphospholipid syndrome